Constraining Evolution of Alternaria alternata Resistance to a Demethylation Inhibitor (DMI) Fungicide Difenoconazole - He, Meng-Han; Wang, Yan-Ping; Wu, E-Jiao; Shen, Lin-Lin; Yang, Li-Na; Wang, Tian; Shang, Li-Ping; Zhu, Wen; Zhan, Jiasui (Frontiers in Microbiology, 2019)
Evolution of fungicide resistance in plant pathogens is one of major concerns in sustainable plant disease management. In this study, the genetics and potential of developing resistance to a demethylation inhibitor (DMI) fungicide, difenoconazole, in the fungal pathogen Alternaria alternata was investigated using a comparative analysis of genetic variation in molecular (Single Sequence Repeats, SSR) and phenotypic (fungicide tolerance) markers. No difenoconazole resistance was found in the 215 A. alternata isolates sampled from seven different ecological zones in China despite the widespread use of the fungicide for more than 20 years. This result suggests that the risk of developing resistance to difenoconazole in A. alternata is low and we hypothesize that the low risk is likely caused by fitness penalties incurred by resistant mutants and the multiple mechanisms involving in developing resistance. Heritability and plasticity account for ~24% and 3% of phenotypic variation respectively, indicating that genetic adaptation by sequence variation plays a more important role in the evolution of difenoconazole resistance than physiological adaptation by altering gene expression. Constraining selection in the evolution of A. alternata resistance to difenoconazole was documented by different patterns of population differentiation and isolate-by-distance between SSR markers and difenoconazole tolerance. Though the risk of developing resistance is low, the findings of significant differences in difenoconazole tolerance among isolates and populations, and a skewing distribution towards higher tolerance suggests that a stepwise accumulation of tolerance to the fungicide might be occurring in the pathogen populations. As a consequence, dynamic management programs guided by evolutionary principles such as spatiotemporal rotations of fungicides with different modes of action are critical to prevent the continued accumulation of tolerance or the evolution of resistance to difenoconazole and other DMI fungicides.